NILAI-NILAI SOSIAL DALAM HADIS NABI : (Studi Hadis tentang perumpamaan Muslim sebagai Tubuh) - Daib Insan Labib, Muhammad Alfreda; Bintara, Anggi Radar; Syamsul, Ilham; Setiadin, M. Arif Rahman (Amerta Media, 2024)
This article discusses about social values contained in the hadith which contains about tamṡīl Muslims as a whole body. Implicitly, the Prophet ordered his people to always care for others. This is because humans as social creatures cannot be separated from the help of fellow creatures. This research method is qualitative with a descriptive-analytical data processing method, namely presenting data that has been collected and then analyzed in depth to achieve the research objectives. This article starts from three basic questions. 1). What related hadiths have been collected in kutub al-tis’ah? 2). What are the social values contained in the hadith